(untitled) (KONFERENSIYA, 2026)
This article explores the theoretical foundations, structural components, and practical implications of digital integrative educational models aimed at promoting healthy lifestyles and sustainable sports development. Using analytical and comparative research methods, the study examines current trends, benefits, and challenges associated with the implementation of digital integrative models in educational institutions. The results demonstrate that such models enhance motivation, personalize physical activity, improve health awareness, and support long-term sports engagement. The study emphasizes the importance of interdisciplinary collaboration, digital competence, and institutional support for the successful implementation of digital integrative educational models.